Count Basie and his orchestra 1964 ; Lionel Hampton and his orchestra 1965 ; Duke Ellington and his famous orchestra 1965 - Basie, Count, 1904-; Hampton, Lionel; Ellington, Duke, 1899-1974.; Swingtime Video (Hollywood, CA. : Swingtime Video, 1984)
Contains big band music by Count Basie, Lionel Hampton and Duke Ellington; taped in 1964-65.
VHS format.
Title on container: The big bands.
Editor, Virgil Sipes ; narrator, Gene Norman.
Keywords: Big band music